PENINGKATAN HASIL BELAJAR BAHASA INDONESIA DENGAN MENGGUNAKAN MEDIA KARTU KATA BEWARNA PADA SISWA KELAS I SD NEGERI 08 PULAU PUNJUNG: IMPROVING THE RESULTS OF LEARNING INDONESIAN BY USING COLORED WORD CARD MEDIA IN GRADE I STUDENTS OF SD NEGERI 08 PULAU PUNJUNG - yusnaini erita (International Journal of Technology Vocational Education and Training, 2022)
The purpose of this study was to improve Indonesian language learning outcomes in grade 1 students of SD Negeri 08 Pulau Punjung in 2019 by using word card media. The form of research is Classroom Action Research which consists of 4 stages, namely planning, implementing actions, observing, and reflecting. The subjects were grade 1 students of SD Negeri 08 Pulau Punjung, Pulau Punjung Subdistrict, Dharmasraya Regency, totaling 30 students consisting of 16 male students and 14 female students. Based on this research, it can be concluded that in the second cycle, the students' learning outcomes and activeness after being given action showed an increase from the first cycle. By using word card media, the average score of students increased from 68.09 to 86.19. The completeness of student learning from the percentage of completeness 100% exceeds the minimum completeness criteria, which is 80%.